Chemical and Structural Evaluation of Internal Fixation Materials for Facial Fractures - Tomáz, Francisnele Maria de Aquino Fraporti; de Oliveira, Helder Fernandes; Aranha, Andreza Maria Fábio; Araújo Estrela, Cyntia Rodrigues de; Meireles Borba, Alexandre; Estrela, Carlos; Guedes, Orlando Aguirre (International Journal of Advanced Engineering Research and Science, 2020)
Oral and maxillofacial injuries often result in fractures tofacial bones. The treatment of facial fractures involves the use of plates and screws for internal fixation. This study was aimedatanalyzing the surface morphology and chemical constitution of internal fixation materials used to treatfacial fractures through scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) analysis. Twenty-seven plates and 21 screws were distributed in six experimental groups: Group 1- Toride®; Group 2- Engimplan®; Group 3- MDT®; Group 4- Promm®; Group 5- Osteomed®andGroup 6- Stryker®. The samples underwent SEM, andthe external surface morphology was analyzed qualitatively in images obtained with a magnification of 30-1000X. The surface was described according to its regularity (regular or irregular) and concerning the presence of defects (scratches, corrosion, metal fragments, metal deformation or protuberance [burrs]). Constitutive analysis was made through EDX. The chemical elements were quantified and presented asatomic weight percentages (%p). All the plates presented external surfaces with irregular aspects. Defects were not observed only in Osteomed® and Stryker® plates. The main components found in the plates were titanium (Ti), silicon (Si) and aluminum (Al). The element phosphorous (P) was found only in Stryker® plates. The screws presented regular surfaces and defects onthe head and threads. Most of the screws presented Ti and Al peaks. Traces of vanadium (V) were identified in the Stryker® and Toride® screws. The Promm® screws were made of Ti. The analyzed plates and screws presented surfaces with different aspects and defects. Some of the chemical elements found in the plates and screws were not described by their manufactures.